Analysis of Oil Palm Production Potential Based on Plantation Area in Major Oil Palm-Producing Provinces of Indonesia - Heri Setyawan; Agus Manto; Wandha Atmaka Aji; Adhitya Kurniadhi; Theofilus Tejo Murti (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Oil palm is one of the leading plantation commodities that contributes significantly to the Indonesian economy. Plantation area is one of the main factors influencing oil palm production. This study aimed to analyze the potential of oil palm production based on plantation area in several major oil palm-producing provinces in Indonesia. A descriptive quantitative approach was employed using secondary data from ten major oil palm-producing provinces in Indonesia in 2024. The variables analyzed included plantation area, production, and oil palm productivity. Data were analyzed using descriptive statistics, Pearson correlation analysis, and simple linear regression. The results showed that Riau Province had the largest plantation area and production, reaching 3,490,000 ha and 9,130,000 tons, respectively, while Central Kalimantan recorded the highest productivity at 3.67 tons/ha. Pearson correlation analysis revealed a very strong positive relationship between plantation area and oil palm production, with a correlation coefficient of r = 0.973. Furthermore, simple linear regression analysis produced the equation Y = 2.7218X + 94,434 with a coefficient of determination (R²) of 0.9476, indicating that 94.76% of the variation in oil palm production could be explained by plantation area.These findings demonstrate that plantation area is the dominant factor affecting oil palm production in the major oil palm-producing provinces of Indonesia. Therefore, increasing oil palm production can be achieved through the optimization of plantation land utilization and improvements in plantation productivity.